Unmarked plural nouns in English and theis difficulties for the 1st year students at the Faculty of Tourism, Honoi University of Culture - Nguyễn, Thanh Tâm (University of Languages and International Studies, 2017)
This paper reports on unmarked plural nouns in English and the difficulties which unmarked plural nouns cause to the 1st year students at the Faculty of Tourism at HUC. The purpose of this study was: (1) to provide learners with grammatical features of unm (...)